OPTIMASI PRODUKSI BIODIESEL DARI BIJI JARAK PAGAR MELALUI TRANSESTERIFIKASI IN SITU MENGGUNAKAN METODE RESPON PERMUKAAN - Ika Amalia Kartika dan Yuyun Pujiastuti (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT Energy consumption increases when human activity increases. Today, the energy supply is mainly focused on fossil fuel which its availability is limited and the price increases continuelly. There is thus a need to develop the alternative energy such as biodiesel. The objective of this study is to determine the optimum process conditions to produce biodiesel from jatropha seeds by in situ transesterification using respon surface method (RSM). The variable of process conditions used was reaction time (A) (45, 50 and 55oC) and hexane to total solvent ratio (B) (1/6, 2/6 and 3/6), while the respon (y) observed included biodiesel yield, acid value, saponification value, viscosity and ash content. Reaction time, stirring speed and KOH concentration were respectively fixed at 3 h, 500 rpm and 0,075 mpl/L methanol. Regression analysis showed that first order polynomial equation, y = 74,98 + 1,20 A – 2,71 B (R2 = 89,87%) was significant to optimize the influence of reaction temperature and hexane to solvent ratio on biodiesel yield. The influence of hexane to solvent ratio on biodiesel yield was more significant then that reaction temperature. Biodiesel yield increased as hexane to solvent ratio decreased. The influence of variable A and B on biodiesel quality, especially saponification value and viscosity, was significant. Highest biodiesel yield (78,60%) was obtained under process conditions of 55oC reaction temperature and 1/6 hexane to solvent ratio. Biodiesel quality under such process conditions was acid value of 0,66 mg KOH/g, saponification value of 195 mg KOH/g, ash content of 0,0% and viscosity of 3,70 cSt. Keyword: biodiesel, transesterification in situ, jatropha, response surface method